Advances in Safety Management and Human Factors Proceedings of the AHFE 2017 International Conference on Safety Management and Human Factors, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA (Advances in Intelligent Systems and Computing,, 2018)
This book discusses the latest findings on ensuring employees' safety, health, and welfare at work. It combines a range of disciplines - e.g. work physiology, health informatics, safety engineering, workplace design, injury prevention, and occupational psychology - and presents new strategies for safety management, including accident prevention methods such as performance testing and participatory ergonomics. The book, which is based on the AHFE 2017 International Conference on Safety Management and Human Factors, held on July 17-21, 2017, in Los Angeles, California, USA, provides readers, including decision makers, professional ergonomists and program managers in government and public authorities, with a timely snapshot of the state of the art in the field of safety, health, and welfare management. It also addresses agencies such as the Occupational Safety and Health Administration (OSHA) and the National Institute for Occupational Safety and Health (NIOSH), as well as other professionals dealing with occupational safety and health.